Framework for unfolding government expenditure for scaling up climate smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We have adopted that framework to review existing policies of government of India and published one journal article on this. This framework has been adopted by the government of Bhutan to prepare their agricultural stategies.